2019
DOI: 10.1002/phar.2224
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Interventions Associated with Cost Avoidance Able to Be Performed in the Intensive Care Unit and Emergency Department

Abstract: A framework for evaluating pharmacists’ impact on cost avoidance in the intensive care unit (ICU) and emergency department (ED) has not been established. This scoping review was registered (CRD42018091217) and conducted to identify, aggregate, and qualitatively describe the highest quality evidence for cost avoidance generated by clinical pharmacists on interventions performed in an ICU or ED. Searches were conducted in PubMed, Scopus, CINAHL, Cochrane Central Register of Controlled Trials, and Cochrane Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 70 publications
0
66
0
1
Order By: Relevance
“…A framework proposed in a recent study was adopted to classify and assess the value of clinical pharmacist interventions in ICUs 12 . Pharmacist interventions were grouped into six main categories: (a) prevention of adverse drug events (ADEs), identified as actions to prevent major ADEs, including inappropriate dosage affecting efficacy or safety, duplication of therapy and drugs prescribed to incorrect patient, as well as to prevent minor ADEs, including minor duplication of therapy, minor drug‐drug, drug‐food or drug‐laboratory interaction, and incorrect patient information (eg weight or age); these actions taken by the pharmacist could prevent temporary or permanent patient harm that may lead to increased length of stay as well as other medical complications due to a medication error or reaction; (b) resource utilization, identified as actions to prevent unnecessary care, avoid unnecessary laboratory tests, switch from intravenous to oral medication route, optimize medication therapy through discontinuation of unwarranted therapy and preventing unnecessary high‐cost medications; (c) individualization of patient care, identified as tailoring medication through dosage adjustment, antibiotic streamlining, new drug therapy recommendations, anticoagulation management and pharmacokinetic monitoring; (d) prophylaxis, identified as reducing the risk of complications in critically ill patients by initiating venous thromboembolism prophylaxis, reducing stress‐related mucosal bleeding, and preventing ventilator‐associated pneumonia; (e) hands‐on care, which involves a broad range of interventions such as bedside interventions not captured by other categories, including participated in emergency blue codes and rapid response teams, educating patients on medication at discharge and following up with patients after discharge; and (f) administrative and supportive tasks, identified as activities of direct patient care that are more administrative or supportive in nature which aim to improve the medication use process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A framework proposed in a recent study was adopted to classify and assess the value of clinical pharmacist interventions in ICUs 12 . Pharmacist interventions were grouped into six main categories: (a) prevention of adverse drug events (ADEs), identified as actions to prevent major ADEs, including inappropriate dosage affecting efficacy or safety, duplication of therapy and drugs prescribed to incorrect patient, as well as to prevent minor ADEs, including minor duplication of therapy, minor drug‐drug, drug‐food or drug‐laboratory interaction, and incorrect patient information (eg weight or age); these actions taken by the pharmacist could prevent temporary or permanent patient harm that may lead to increased length of stay as well as other medical complications due to a medication error or reaction; (b) resource utilization, identified as actions to prevent unnecessary care, avoid unnecessary laboratory tests, switch from intravenous to oral medication route, optimize medication therapy through discontinuation of unwarranted therapy and preventing unnecessary high‐cost medications; (c) individualization of patient care, identified as tailoring medication through dosage adjustment, antibiotic streamlining, new drug therapy recommendations, anticoagulation management and pharmacokinetic monitoring; (d) prophylaxis, identified as reducing the risk of complications in critically ill patients by initiating venous thromboembolism prophylaxis, reducing stress‐related mucosal bleeding, and preventing ventilator‐associated pneumonia; (e) hands‐on care, which involves a broad range of interventions such as bedside interventions not captured by other categories, including participated in emergency blue codes and rapid response teams, educating patients on medication at discharge and following up with patients after discharge; and (f) administrative and supportive tasks, identified as activities of direct patient care that are more administrative or supportive in nature which aim to improve the medication use process.…”
Section: Methodsmentioning
confidence: 99%
“…All considered costs were calculated based on acquisition costs. For each category, the average cost reported in a scoping review of landmark studies was assumed 12 . This scoping review by Hammond et al is the most recent study to identify, aggregate and qualitatively define quality evidence of cost avoidance made by clinical pharmacists on interventions performed in an ICU or emergency department.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we indicated previously, the scoping review from Pharmacotherapy showed that 33 of the 38 intervention categories of cost avoidance were supported by very low rigor sources, including expert opinion sources (level IV evidence) and by descriptive, noncomparative articles (level III evidence). 3 Neither of those types of evidence have any credibility when attempting to justify investment in clinical pharmacy services. The notion that data from these sources represent "almost exact cost avoidance" as suggested by Hammond and Rech in their letter, is simply ridiculous hyperbole.…”
mentioning
confidence: 99%
“…Preventing untoward complications and adverse drug effects is a concern of all clinicians from the standpoint of patient outcomes but also with regard to health care costs. A unique article included in this themed issue provides a framework for mitigating costs by introducing strategies for pharmacists, or really any clinician, to document their worth on the basis of cost avoidance. Of note, cost‐avoidance interventions should not be the responsibilities of a particular profession but a responsibility of the health care team.…”
mentioning
confidence: 99%